Small Corporations: Better Controlling the Spigot of ‘Red Tape’ - Clarke , Andrew (Journal of Law and Governance, 2009)
Regulation in Australia appears to be increasing at an exponential rate. For small businesses that, are often resource poor and isolated, compliance is a burden. They face a paradigm conflict with regulators, who often are imbued with the objective of maintaining quality standards and perceptions of servicing an industry, while the regulated see regulation as an evil and a cost to doing business. Two case studies illustrate the political minefields in alternative approaches to regulation. Finally, the paper reviews changes in regulation internationally and in Australia and puts forward some innovative options for the future implementation of regulation of small businesses.